Ultrasonic chemical oxidative degradations of 1,3-dialkylimidazolium ionic liquids and their mechanistic elucidations - Li, X; Zhao, J; Li, Q; Wang, L; Tsang, S (2007)
A highly efficient process for oxidative degradation of 1,3-dialkylimidazolium ionic liquids in hydrogen peroxide/acetic acid aqueous medium assisted by ultrasonic chemical irradiation is, for the first time, described. It is shown that more than 93% of the 1,3-dialkylimidazolium cation with the corresponding Cl-, Br-, BF4- and PF6- counter-anions at a concentration of 2.5 mM can be degraded at 50 °C within 12 h while at 72 h the conversions approach 99%. A tentative mechanism for the degradation of these ILs is for the first time proposed through a detailed kinetic analysis of several characteristic transients and/or immediate products, which are identified during the ILs degradation using GC-MS. The results clearly indicate that three hydrogen atoms in the imidazolium ring are the first sites preferably oxidized, followed by cleavage of the alkyl groups attached to the N atoms from the ring. The nature of the alkyl chain length on the imidazolium ring and the type of counter anion do not seem to affect the degradation process. Further, selective fragmentations of C-N bonds of the imidazolium or derived ring lead to ring opening, forming degraded intermediates. It is also shown that acetoxyacetic acid and biurea are the final kinetically stable degraded products from the ILs under the degradation conditions. © The Royal Society of Chemistry 2007.